Dysregulation of miR-146a by periodontal pathogens: A risk for acute coronary syndrome - Bagavad Gita, J; George, Ann V; Pavithra, N; Chandrasekaran, S C; Latchumanadhas, K; Gnanamani, A (Journal of periodontology (1970), 2019)
Periodontitis is a polymicrobial, chronic inflammatory disease leading to loss of tooth-supporting structures. The bacteremia, endotoxemia, and systemic low-grade inflammation associate periodontitis with systemic illnesses such as diabetes mellitus and coronary artery disease. Periodontal pathogens have been detected from atheromatous plaque by amplification of the genetic material by using specific oligonucleotide primers in polymerase chain reaction. Though the association between periodontitis and cardiovascular diseases has been ascertained by systematic reviews and meta-analyses, its pathophysiology is not lucid. MicroRNAs are currently implicated in the regulation of many cellular processes including inflammation and may play a vital role in our understanding of this disease association. In this case-control study, we explored the role of the inflammatory microRNA, miR-146a, in acute coronary syndrome (ACS) subjects with and without chronic periodontitis (CP) and its regulation of the innate immune host response to periodontal pathogens. Three groups each comprising 66 patients each, namely group 1 (ACS patients without CP), group 2 (ACS patients with CP) and group 3 (CP only) formed the study population. Subgingival plaque samples and serum samples were subjected to quantitative Polymerase Chain Reaction (qPCR) for detection of Porphyromonas gingivalis, a keystone pathogen and to assess the levels of circulating miR-146a and associated proinflammatory cytokines. miR-146a associated significantly in group 2 subjects with an odds ratio 1.434, 95% confidence interval 1.013-2.030, P < 0.042, and a predictive percentage of 83.3% and group 1 with a predictive percentage of 76.0.% The associated cytokines interleukin-6 (IL-6), tumor necrosis factor-α, and IL-1β also showed an upregulation with statistical significance (P < 0.05). microRNA-146a is a key molecule associating periodontitis with acute coronary syndrome.